A Study on the Provenance of Early to Late Triassic Clastic Rocks From the Northwestern Sichuan Basin, Southwestern China: Constraints on the Early Mesozoic Tectonic Evolution of the Western Yangtze Block - Meng, Lifeng; Chen, Wei; Shen, Tong; Cai, Jinfa (Frontiers in Earth Science, 2022)
U-Pb ages of 637 new detrital zircons from Early Triassic and Late Triassic sandstone in the Northwestern Sichuan Basin (NWSB), together with the petrology and paleocurrent data, are used to constrain the sediment provenance and tectonic-paleogeographic evolution of the western Yangtze block. The U-Pb age data for the Lower Triassic detrital zircons generally show populations at ~1850 Ma, 980-705 Ma, 680-510 Ma and 290-230 Ma with a minor cluster at ~2.4 Ga. Such age spectrum features together with the eastward to northeastward paleocurrent direction implied that the Northwestern Sichuan Basin was dominantly fed by the uplifted Khamdian Paleoland. While the Upper Triassic detrital zircons yield age populations of 855-730 Ma, 455-415 Ma, 290-215 Ma and a prominent age group of 1.9-1.7 Ga together with paleocurrent and internal difference between samples from different region indicated a major source of the Longmenshan thrust belt and SongPan-Ganzi terrane for the south area of the NWSB while Qinling orogenic belt for the north part of NWSB. Such transition of the provenance from Early Triassic to Late Triassic probably indicated the subsidence of the Khamdian Paleoland and uplifted of Songpan-Ganzi terrane and Qinling orogenic belt. Such inversion most likely resulted from the delayed thermal subsidence of the Emeishan Large Igneous Province (ELIP) and the gravitational loading triggered by the eastward shortening of the Songpan-Ganzi terrane as well as the ongoing convergence between Yangtze and North China blocks.